Pengaruh Adversity Quotient Terhadap Hasil Belajar Matematika SMPN 1 Narmada Tahun Ajaran 2019/2020 - Iftahul Muhayana; Nyoman Sridana; Sudi Prayitno; Amrullah Amrullah (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This research aimed to determine the influence of adversity quotient (AQ) on student mathematics learning achievement (MLA) of class VIII SMP Negeri 1 Narmada academic year 2019/2020. Population in this study consisted of 379 students and sample of the research is consisted of 80 students which are selected by using the purposive sampling technique. Data collection techniques in this research using questionnaires and test. The instrument of this research using a closed AQ questionnaire consisting of 50 statements and essay of pattern and sequence mathematics number consisting of 4 questions. The data obtained was analyzed using correlation and simple linear regression. Correlation coefficient (r) equal to 0,799, which indicate that relation between AQ on student MLA including was strong category. The contribution of AQ on student MLA, coefficient of determination is 60,684 %. This indicated AQ also affect the student’s MLA of class VIII SMP Negeri 1 Narmada academic year 2019/2020 shown by liniear regression equation in this research is Y=-20,592+0,577X